2018
DOI: 10.7150/jca.23481
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differential Expressions of Long Non-coding RNAs in Nasopharyngeal Carcinoma Using Next-generation Deep Sequencing

Abstract: Background: Little knowledge about long non-coding RNAs(lncRNAs) in nasopharyngeal carcinoma (NPC) has been acquired.Methods: Next-generation sequencing was applied in 7 cases of NPC tissues and 7 cases of normal tissues in nasopharynx. PLEX, CNCI and CPAT soft-wares were used to predict novel lncRNAs. Real-time Quantitative PCR (qPCR) further validated the data in 20 cases of NPC tissues and 14 cases of normal tissues. Then the cis-regulators and trans-regulators and potential biological functions together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Studies have shown that asiatic acid notably reduces the viability of cisplatin-resistant NPC cells by inducing apoptosis via the internal and external apoptotic pathways [ 57 ]. The proto-oncogene JUN is associated with the cis-regulatory lncRNA RP4-794H19.1 and is very commonly found in cancers; JUN has been linked to the TNF signaling pathway, and may be a vital gene in NPC [ 58 ]. TNF-α may be a tumor-promoting factor in NPC, as TNF-α expression has been observed in both primary NPC specimens and serum derived from NPC patients, and can significantly predict the risk of distant metastasis in NPC patients [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that asiatic acid notably reduces the viability of cisplatin-resistant NPC cells by inducing apoptosis via the internal and external apoptotic pathways [ 57 ]. The proto-oncogene JUN is associated with the cis-regulatory lncRNA RP4-794H19.1 and is very commonly found in cancers; JUN has been linked to the TNF signaling pathway, and may be a vital gene in NPC [ 58 ]. TNF-α may be a tumor-promoting factor in NPC, as TNF-α expression has been observed in both primary NPC specimens and serum derived from NPC patients, and can significantly predict the risk of distant metastasis in NPC patients [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, LncRNA HOX transcript antisense intergenic RNA (HOTAIR) acts as an oncogene, whose high abundance in NPC cells and the patient tumor samples correlates with a poor prognosis [7,8]. With the advance of microarray and high-throughput RNA sequencing, a large number of lncRNAs have been identified in NPC tissues and cell lines [9]. However, the roles of these dysregulated lncRNAs in the pathogenesis of NPC remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“… 10 LINC01410 overexpression can also facilitate the proliferation and invasion of EC cells. 11 Notably, the emerging evidences have displayed that LINC01106 is related to the occurrence and progression of several cancers, such as nasopharyngeal carcinoma, 12 lung adenocarcinoma 13 and colorectal cancer. 14 However, whether LINC01106 involves in regulating EC progression has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%